2019
DOI: 10.24251/hicss.2019.481
|View full text |Cite
|
Sign up to set email alerts
|

Repairing the Digital Divide Can Increase the Service Divide: The Effects of Patient Portals on Kidney Allocation

Abstract: The severe shortage of organs combined with increasing demand for them characterize the outcomes for the kidney allocation process. Despite the efforts to improve the allocation of kidneys, notable inefficiencies and unequal access to available organs persist across patient populations. The goal of this study is to examine (i) whether the adoption of a patient-oriented information technology (IT), namely the patient portals, can mitigate inefficiencies in the allocation of these scarce resources (kidneys) in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…Amongst these are the observed adverse impacts of patient portals on health equity [62,63]. Whilst portals may benefit some user groups, they might simultaneously increase health disparities in other groups [64]. Some studies have also found potential adverse impacts on patient-provider relationships [63].…”
Section: Studying Unanticipated Consequences and Impacts Of System In...mentioning
confidence: 99%
“…Amongst these are the observed adverse impacts of patient portals on health equity [62,63]. Whilst portals may benefit some user groups, they might simultaneously increase health disparities in other groups [64]. Some studies have also found potential adverse impacts on patient-provider relationships [63].…”
Section: Studying Unanticipated Consequences and Impacts Of System In...mentioning
confidence: 99%